TINJAUAN HUKUM ISLAM TERHADAP LARANGAN PERNIKAHAN ADAT BATAK TOBA (STUDI KASUS MASYARAKAT MUSLIM DESA SETIA KECAMATAN PAHAE JAE KABUPATEN TAPANULI UTARA) - Sholihin Gultom (Jurnal At-Tabayyun, 2019)
This Writing entitled "The views of Islamic Law Marriage Against Prohibition In Indigenous Toba Batak (Case study of Muslim societies Village Setia Subdistrict Pahae Jae District North Tapanuli)". This thesis observe the customary marriage ban offenders Batak Toba and the observation of several informants. Principal issue in this study is (1). How customary law marriage in Muslim society Batak Toba, village Setia Subdistrict Pahae Jae Regency Tapanuli North. (2). What are the factors and sociological background of customary marriage ban for the Muslim community Batak Toba Village Setia Subdistrict Pahae Jae Regency Tapanuli North. (3). What does the Islamic law on customary marriage law in Muslim society Toba Batak Village Setia Subdistrict Pahae Jae Regency Tapanuli North. This research is empirical legal research, known as non-doctrinal research. Therefore this study is to describe systematically descriptive, factual and accurate to cases in which the issues examined included the properties, characteristics and certain factors. So the method to collect the data is qualitative research method is an approach that is not done by using formulas and statistical symbols. In the final conclusion is that the rules of customary marriages for Muslims Batak Toba Village Faithful, there is "customary marriage ban". Although the terms and pillars have been met according to Islamic law, but the Muslim community Batak Toba Village Setia not necessarily allow the conduct of the marriage.